CLINICOPATHOLOGICAL FACTORS AFFECTING SURVIVAL OUTCOMES OF ESOPHAGEAL CANCER PATIENTS TREATED AT A SINGLE TERTIARY RADIOTHERAPY CENTER IN IRAQ - Mikaeil, Redeer Adnan; Saeed, Kamal Ahmad; Saeed, Nyan Othman (Journal of Sulaimani Medical College, 2025)
Background Carcinoma of the oesophagus is one of the top ten most prevalent and aggressive types of cancer worldwide. Objectives To determine the clinicopathological factors affecting the survival of oesophagal cancer. Patients and Methods This cross-sectional study was conducted retrospectively on 97 patients with oesophagal cancer in a single radiotherapy cancer centre in Sulaimaniyah City, Kurdistan region of Iraq, from 2010 to 2021. Results The mean age of the patients was 68.4 ± 12.2, ranging from 29 to 90 years old. The major histology was squamous cell carcinoma (89%), and pathological grade II disease was more prevalent (53%). Males and females were equally affected (50% for each gender). At presentation, a larger number of the patients were located in the lower (N=30) and mid (N=29) oesophagus. Stage III was the most common presenting stage (45.7%). The median follow-up time was 14 months. The 12-month and 18-month survival rates were 58.6% and 34.6%, respectively. There was a significantly better survival outcome for patients with grade 1 disease than higher grades, especially grade 2 (p value= 0.01). Chemoradiation showed significantly improved survival benefits compared with RT alone (p value= 0.03) and tri-modality therapy. Conclusion The most significant factors affecting 18-month actual survival in oesophagal cancer are tumour biology characteristics, especially low tumour grade, and chemoradiotherapy without surgery.
Keywords: Esophageal cancer; clinicopathological factors; radiotherapy; survival outcomes